Evaluating multiple spatial scales to understand the distribution of anuran beta diversity in the Brazilian Atlantic Forest - Melchior, Lara G. [UNESP] (2017)
We partitioned the total beta diversity in the species composition of anuran tadpoles to evaluate if species replacement and nestedness components are congruent at different spatial resolutions in the Brazilian Atlantic Forest. We alternated the sampling grain and extent of the study area (among ponds at a site, among ponds within regions, among sites within regions, and among sites within regions pooled together) to assess the importance of anuran beta diversity components. We then performed variation partitioning to evaluate the congruence of environmental descriptors and geographical distance in explaining the spatial distribution of the species replacement and nestedness components. We found that species replacement was the main component of beta diversity, independent of the sampling grain and extent. Furthermore, when considering the same sampling grain and increasing the extent, the values of species replacement increased. On the other hand, when considering the same extent and increasing the sampling grain, the values of species replacement decreased. At the smallest sampling grain and extent, the environmental descriptors and geographic distance were not congruent and alternated in the percentage of variation explaining the spatial distribution of species replacement and nestedness. At the largest spatial scales (SSs), the biogeographical regions showed higher values of the percentage explaining the variation in the beta diversity components. We found high values of species replacement independently of the spatial resolution, but the processes driving community assembly seem to be dependent on the SS. At small scales, both stochastic and deterministic factors might be important processes structuring anuran tadpole assemblages. On the other hand, at a large spatial grain and extent, the processes restricting species distributions might be more effective for drawing inferences regarding the variation in anuran beta diversity in different regions of the Brazilian Atlantic Forest.